2010
DOI: 10.1007/s12272-010-0402-3
|View full text |Cite
|
Sign up to set email alerts
|

Chemical components from the Vietnamese soft coral Lobophytum sp.

Abstract: Chromatographic separation resulted in the identification of one new squalene derivative, named lobophytene (1), three cembranoid diterpenes (2-4), and two sterols (5 and 6) from the Vietnamese marine soft coral Lobophytum sp. Their structures were identified on the basis of extensive spectroscopic data and comparison of those with reported data. Compounds 1 and 2 showed significant cytotoxic activities against lung (A549) and colon (HT-29) cell lines with IC(50) values of 8.2 and 5.6 microM for 1; 5.1 and 1.8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 20 publications
1
10
0
1
Order By: Relevance
“…The 1 H, 13 C, and HSQC NMR revealed the presence of a ketone carbonyl carbon ( δ C 209.9), two ester carbonyl carbons ( δ C 170.0 and δ C 169.5), three pairs of C=C double bonds [ δ C / δ H 135.2 (C-8), 135.1 (C-15), 130.3 (C-11)/5.20 (H-11, t, J = 6.3 Hz), 129.3 (C-12), 125.7 (C-7)/4.98 (H-7, m), and 124.8 (C-3)/5.73 (H b -3, d, J = 2.5 Hz), 6.42 (H a -3, d, J = 2.5 Hz)], two oxymethines [ δ C / δ H 80.2 (C-2)/4.97 (H-2, d, J = 3.5 Hz), 75.6 (C-14)/5.09 (H-14, dt, J = 11.0, 2.5 Hz)], three tertiary methyls [ δ H 2.02 (H-14-OAc, s), 1.72 (H-20, s), and 1.49 (H-19, s)], and a secondary methyl at δ H 1.14 (H-18, d, J = 7.0 Hz) (Table 2). Detailed analysis of these NMR data suggested that 2 also displayed a type IIa cembranoid skeleton and was closely related to a previously reported compound, (1 S ,2 S ,3 E ,7 E ,11 E )-3,7,11,15-cembratetraen-17,2-olide [80], with a missing C=C double bond moiety, as well as additional groups of a ketone carbonyl ( δ C 209.9) and an acetyl [ δ C / δ H 170.0, 21.0/2.02 (s)]. According to the HMBC cross-peaks (from H-18 and H-2 to C-3; from H-2 to C-14), two additional oxygen bearing groups were added into the main 14-membered ring system, a ketone group at C-3 and an acetyl group at C-14 (Figure 4).…”
Section: Resultssupporting
confidence: 84%
“…The 1 H, 13 C, and HSQC NMR revealed the presence of a ketone carbonyl carbon ( δ C 209.9), two ester carbonyl carbons ( δ C 170.0 and δ C 169.5), three pairs of C=C double bonds [ δ C / δ H 135.2 (C-8), 135.1 (C-15), 130.3 (C-11)/5.20 (H-11, t, J = 6.3 Hz), 129.3 (C-12), 125.7 (C-7)/4.98 (H-7, m), and 124.8 (C-3)/5.73 (H b -3, d, J = 2.5 Hz), 6.42 (H a -3, d, J = 2.5 Hz)], two oxymethines [ δ C / δ H 80.2 (C-2)/4.97 (H-2, d, J = 3.5 Hz), 75.6 (C-14)/5.09 (H-14, dt, J = 11.0, 2.5 Hz)], three tertiary methyls [ δ H 2.02 (H-14-OAc, s), 1.72 (H-20, s), and 1.49 (H-19, s)], and a secondary methyl at δ H 1.14 (H-18, d, J = 7.0 Hz) (Table 2). Detailed analysis of these NMR data suggested that 2 also displayed a type IIa cembranoid skeleton and was closely related to a previously reported compound, (1 S ,2 S ,3 E ,7 E ,11 E )-3,7,11,15-cembratetraen-17,2-olide [80], with a missing C=C double bond moiety, as well as additional groups of a ketone carbonyl ( δ C 209.9) and an acetyl [ δ C / δ H 170.0, 21.0/2.02 (s)]. According to the HMBC cross-peaks (from H-18 and H-2 to C-3; from H-2 to C-14), two additional oxygen bearing groups were added into the main 14-membered ring system, a ketone group at C-3 and an acetyl group at C-14 (Figure 4).…”
Section: Resultssupporting
confidence: 84%
“…This type of FPT inhibition enhanced interest in this group of metabolites [86]. Other species of this genus also showed cembranolide diterpenes (lobophytene) with significant cytotoxic activity against human lung adenocarcinoma (A549) and human colon adenocarcinoma (HT-29) cell lines [56]. Lobophytum durum and Lobophytum crassum produce durumolides A–C [60], durumhemiketalolide A–C [61] and crassumolides A and C [58], with anti-inflammatory effects.…”
Section: Class Anthozoamentioning
confidence: 99%
“…Những công bố quốc tế trên các đối tượng động vật biển sống ở biển Việt Nam rất hạn chế với những công trình tiêu biểu sau: Chất triterpene glycosides từ hải sâm Holothuria scabra ở Cát Bà, Hải Phòng [74], một chất squalene mới có khả năng kháng lại tế bào ung thư phổi và ung thư trực tràng, 3 cembranoid diterpenes và 2 sterols từ san hô mềm Lobophytum sp. ở Cồn Cỏ, Quảng Trị [75]. Một số các chất mới và cả các chất đã được công bố có hoạt động kháng lại nhiều dòng tế bào ung thư khác nhau từ san hô mềm Lobophytum laevigatum ở Khánh Hòa [76,77].…”
Section: Cơ Hội Và Thách Thức đốI Với Nghiên Cứu Trong Nướcunclassified